Interpersonal relationships between registered nurses and student nurses in the clinical setting-A systematic integrative review - Rebeiro, G.; Edward, K.; Chapman, Rose; Evans, A. (Churchill Livingstone, 2015)
Background: A significant proportion of undergraduate nursing education occurs in the clinical setting in the form of practising skills and competencies, and is a requirement of all nursing curriculum for registration to practice. Education in the clinical setting is facilitated by registered nurses, yet this interpersonal relationship has not been examined well. Objective: To investigate the experience of interpersonal relationships between registered nurses and student nurses in the clinical setting from the point of view of the registered nurse. Design: Integrative review. Review methods: The databases of MEDLINE, CINAHL and OVID were searched. Key words used included: Registered Nurse, Preceptor, Buddy Nurse, Clinical Teacher, Mentor, Student Nurse, Nursing Student, Interpersonal Relationships, Attitudes and Perceptions. Additional review of the literature was manually undertaken through university library textbooks. Results: 632 abstracts were returned after duplicates were removed. Twenty one articles were identified for full text read (quantitative n = 2, mixed n = 6, qualitative n = 14); of these, seven articles addressed the experience of interpersonal relationships between registered nurses and student nurses in the clinical setting from the point of view of the registered nurse and these were reviewed. Conclusions: Providing education for registered nurses to enable them to lead student education in the clinical setting communicates the organizational value of the role. Registered nurses identified being supported in having the time-to-teach were considered important in facilitation of the clinical teaching role.The integrative review did not provide evidence related to the impact diverse clinical settings can have on the relationships between registered nurses and student nurses revealing an area for further examination.